PROFESIONALITAS GURU SEKOLAH DASAR BERSERTIFIKASI DI KOTA BANJARMASIN - Siti Rahmah (Universitas Lambung Mangkurat, 2013)
This study aimed to determine the professionalism of teachers SDN who certified in Banjarmasin. The research data were described consists of a group of pedagogical competence of teachers certified through portfolios, education and training, and passed for consideration age and years of service. The data analysis technique used is descriptive, by using descriptive statistics to describe the data of the study variables. The survey results revealed pedagogical competence of teachers certified through a portfolio categorized either as much as 84%, through education and training 78%, and due consideration of age and years of 72%. From the data the description of the research data revealed that the average score (mean) pedagogical competence of teachers certified through a portfolio of 150.26, 147.30 through education and training and pedagogical competence of teachers due consideration age and years of 144.56, which exceeded the mean The average (mean) ideal is 113. Based on these data pedagogical competence of teachers SDN District of West Banjarmasin classified as either category and has competence above average competence of teachers in general.Key words: professionalism and certified teachers